2015
DOI: 10.1007/s10237-015-0674-0
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of leaflet microstructure and constitutive model on the closing behavior of the mitral valve

Abstract: Recent long-term studies showed an unsatisfactory recurrence rate of severe mitral regurgitation 3–5 years after surgical repair, suggesting that excessive tissue stresses and the resulting strain-induced tissue failure are potential etiological factors controlling the success of surgical repair for treating mitral valve (MV) diseases. We hypothesized that restoring normal MV tissue stresses in MV repair techniques would ultimately lead to improved repair durability through the restoration of MV normal homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 66 publications
3
74
0
Order By: Relevance
“…This is not only important to ECM mechanics but also coupling to the interstitial cell (MVIC) population. We have recently shown that simulated MVIC moduli for the four layers were found to be all within a narrow range of 4.71–5.35 kPa, suggesting that MVIC deformation is primarily controlled by each tissue layer’s respective structure and mechanical behavior rather than the intrinsic MVIC stiffness [67]. This novel result further suggests that while the MVICs may be phenotypically similar throughout the leaflet, they experience layer-specific mechanical stimulatory inputs due to distinct extracellular matrix architecture and mechanical behaviors of the four MV leaflet tissue layers.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only important to ECM mechanics but also coupling to the interstitial cell (MVIC) population. We have recently shown that simulated MVIC moduli for the four layers were found to be all within a narrow range of 4.71–5.35 kPa, suggesting that MVIC deformation is primarily controlled by each tissue layer’s respective structure and mechanical behavior rather than the intrinsic MVIC stiffness [67]. This novel result further suggests that while the MVICs may be phenotypically similar throughout the leaflet, they experience layer-specific mechanical stimulatory inputs due to distinct extracellular matrix architecture and mechanical behaviors of the four MV leaflet tissue layers.…”
Section: Discussionmentioning
confidence: 99%
“…Two dimensional characterization that focuses on the leaflets unfolded into a plane has been carried out with small angle light scattering (SALS). [34,35] Recent efforts have been made to map 2D SALS data to 3D image-derived models, [36] using control points and interpolation. However, these mappings exclude the mitral valve chordae and artefacts from excision such as the relaxation of collagen fibers and subsequent re-orientation remain.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al reported a patient‐specific FE model of a healthy human MV reconstructed from multi‐slice CT scans with detailed leaflet thickness, chordal information, and mitral annulus dynamic motion. Micro‐CT is another widely used modality that can provide detailed MV leaflets and chordal structure for in vitro/ex vivo MV imaging but is usually unavailable with in vivo imaging when using ECHO and MRI . Manually constructing MV geometry from limited imaging data is not an optimal way, because it is highly dependent on the operators' experience, and usually associated with low reproducibility and reliability.…”
Section: Structure‐only MV Modelsmentioning
confidence: 99%